2019
DOI: 10.3390/ijms20246141
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Disease Progression and Resistance to Tyrosine Kinase Inhibitor Therapy in Chronic Myeloid Leukemia: An Update

Abstract: Chronic myeloid leukemia (CML) is characterized by the presence of the BCR-ABL1 fusion gene, which encodes a constitutive active tyrosine kinase considered to be the pathogenic driver capable of initiating and maintaining the disease. Despite the remarkable efficacy of tyrosine kinase inhibitors (TKIs) targeting BCR-ABL1, some patients may not respond (primary resistance) or may relapse after an initial response (secondary resistance). In a small proportion of cases, development of resistance is accompanied or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 175 publications
(192 reference statements)
1
68
0
1
Order By: Relevance
“…Philadelphia-positive (Ph+) chronic myeloid leukemia (CML) is a clonal myeloproliferative disease marked by chromosome translocation t(9;22) (q22;q11) that leads to the BCR-ABL1 fusion gene. The resulting BCR-ABL1 fusion protein (p210), is a constitutively activated tyrosine kinase that drives the leukemic transformation of hematopoietic stem cells, and induces the progression of the disease from the early chronic phase (CP) to the blastic phase (BP) which fatally close the course of the disease [ 1 , 2 , 3 , 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Philadelphia-positive (Ph+) chronic myeloid leukemia (CML) is a clonal myeloproliferative disease marked by chromosome translocation t(9;22) (q22;q11) that leads to the BCR-ABL1 fusion gene. The resulting BCR-ABL1 fusion protein (p210), is a constitutively activated tyrosine kinase that drives the leukemic transformation of hematopoietic stem cells, and induces the progression of the disease from the early chronic phase (CP) to the blastic phase (BP) which fatally close the course of the disease [ 1 , 2 , 3 , 4 ].…”
mentioning
confidence: 99%
“…In recent decades, a high number of biological studies have been done to elucidate the molecular mechanisms of CML pathogenesis and progression [ 16 , 17 , 18 ]. The results of these studies were fundamental to understand how and why the p210 tyrosine kinase protein is able to drive the leukemic transformation of Ph+ hematopoietic progenitors by altering cell proliferation, apoptosis, adhesion and inducing genomic instability [ 1 , 2 ]. Now, we can say that these studies paved the way for the current target therapy [ 19 ].…”
mentioning
confidence: 99%
“…EZH2 is a histone methyltransferase and a component of the polycomb repressive complex 2 (PRC2) for histone H3 methylation (H3K27me3) and transcription inactivation [ 17 , 206 , 207 , 208 ]. EZH2 hyperactivity blocks myeloid differentiation to promote LSC expansion, survival and TKI-resistance [ 17 , 43 , 207 , 208 , 209 , 210 , 211 ]. In vitro studies showed that EZH2 inhibitor EPZ-6438 upregulated tumour suppressor p16 to deplete leukaemic cells in K562, HEL, Kasumi-1, ME-1, Mv4-11 and MOLM13 cell lines [ 207 , 210 ].…”
Section: Targeting CML Stem Cells Via Epigenetic Ribosomal and Trmentioning
confidence: 99%
“…Another in vitro study showed 20–40% reduction in CD34 + cells and 60–80% reduction in progenitor granulocyte/erythroid/megakaryocyte/macrophage (GEMM) and total colony forming cell (CFC) [ 43 ]. Combination with TKI increased activation of H3K27me3 targets (e.g., CDKN2A) and upregulated pro-apoptotic targets of p53 (e.g., NOXA, p53 upregulated modulator of apoptosis (PUMA), BAX, CDKN2A, TNFRS10B), showing >70% reduction in CD34 + /CD38 − /CD45 + cells, near complete eradication of CD34 + /CD45 + cells and restoration of TKI-sensitivity [ 43 , 211 ]. Murine xenograft models with CD34 + cells showed similar findings [ 43 ].…”
Section: Targeting CML Stem Cells Via Epigenetic Ribosomal and Trmentioning
confidence: 99%
“…Despite sufficient inhibition of BCR-ABL1 protein, many patients can still experience failure of the treatment due to development of BCR-ABL1-independent mechanisms of TKIs resistance. Thus far, these non-mutational mechanisms have been more extensively studied in CML than in Ph+ ALL, and are described in great detail elsewhere [139,148,149]. Alternative activation of the BCR-ABL1 downstream pathways, including JAK/STAT, SRC, MAPK, or PI3K seems to be crucial in mediating this particular resistance phenotype, which explains better efficacy of less selective TKIs [150][151][152].…”
Section: Resistance To Tkis In CML and Ph+ B-allmentioning
confidence: 99%